The adrenal cortex: Physiology and diseases in human pregnancy. (September 2019) - Levin, Gabriel; Elchalal, Uriel; Rottenstreich, Amihai
Abstract: Pregnancy is characterized by marked alterations in the hypothalamic–pituitary–adrenal axis and in the function of the adrenal gland. Some of those alterations have clinical characteristics that are similar to those of adrenal gland disorders. While adrenal disorders are rare among pregnant women, they harbor the potential for significant morbidity if they remain unrecognized and untreated. As the majority of patients with adrenal disorders present with clinical features that are typical of normal pregnancy - diagnosis during pregnancy is not uncommonly delayed. A high index of suspicion must be practiced for these disorders as they might carry severe obstetrical negative outcomes. In this review we will survey the normal function of adrenal glands in pregnancy and the role of adrenal hormones in pregnancy. We will outline the adrenal disorders that commonly present during pregnancy and review the literature on treatment modalities.